Assessment of Periodic Open Cellular Structures for Enhanced Heat Conduction in Catalytic Fixed‐Bed Reactors1. Issue 4 (29th September 2015) - Bianchi, Enrico; Schwieger, Wilhelm; Freund, Hannsjörg
Abstract : In this paper, the effective heat conductivity of periodic open cellular structures (POCS) is investigated by means of a systematic numerical study. 3D geometries of different configurations were considered, representing the unit cell volume of the modular POCS. Special emphasis is put on the strut morphology, i.e. the strut cross sectional shape and the distribution of the solid material along the strut. At the same porosity, the optimal designed structures show a higher effective heat conductivity than conventional open‐cell solid foams with random cell geometry. This possibility to exceed the effective thermal conductivity of state‐of‐the‐art open‐cell foams by optimization of their geometrical properties is an interesting novel aspect of high relevance regarding their application in catalytic reactors. Abstract : Numerical simulations show that the effective thermal conductivity of periodic open cellular structures depends not only on the solid fraction, but also significantly on the distribution of the solid along the strut. Thus, literature correlations established for non‐ideal open‐cell foams cannot be applied to ideal cellular structures.